2018
DOI: 10.1111/cns.13065
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dorsal root ganglion stimulation and dorsal column spinal cord stimulation in a model of experimental painful diabetic polyneuropathy

Abstract: Summary Aims Conventional dorsal root ganglion stimulation (DRGS) is known to achieve better pain‐paresthesia overlap of difficult‐to‐reach areas like the feet compared to dorsal column spinal cord stimulation (SCS). As in painful diabetic polyneuropathy (PDPN) pain is mostly present in the feet, we hypothesized that DRGS is more effective in relieving pain in PDPN when compared to SCS. Methods Diabetes was induced in female Sprague‐Dawley rats with an intraperitoneal injection of 65 mg/kg of streptozotocin (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…In the present study, the DRGS mid-frequency was set at 20 Hz, which is the frequency most frequently used for DRGS in humans (7,8,17,21,22). In previous DRGS-animal studies, frequencies of 20-50 Hz were used, which resulted in a significant reversal of neuropathic pain behavior (11,17). Until now there is little data about the use of HF for DRGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the DRGS mid-frequency was set at 20 Hz, which is the frequency most frequently used for DRGS in humans (7,8,17,21,22). In previous DRGS-animal studies, frequencies of 20-50 Hz were used, which resulted in a significant reversal of neuropathic pain behavior (11,17). Until now there is little data about the use of HF for DRGS.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of the stimulation frequency might result in additional beneficial effects in experimental PDPN. The results of a recently published experimental study showed that conventional DRGS (50 Hz) is equally effective as conventional SCS (40–50 Hz) in reduction of PDPN‐associated mechanical hypersensitivity in experimental PDPN. Both SCS and DRGS induced a complete reversal of mechanical hypersensitivity, which was obtained after 15 min in the SCS group vs. after 30 min in the DRGS group.…”
Section: Introductionmentioning
confidence: 99%
“…Under general anesthesia, bipolar electrode was implanted unilaterally at the L5 DRG, according to the earlier described procedure adapted from Pan et al In short, via a paravertebral incision the intervertebral foramen was exposed, the foramen was opened, and the anode and cathode were implanted at the DRG. The electrode was then secured into the transverse process followed by closure of the incision in layers.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison with previous experimental studies regarding neurostimulation in PDPN animals, we used time and design as in previous (published) experiments . Animals were stimulated for 30 minutes at days 3 and 4 following implantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation